An essential, multicomponent signal transduction pathway required for cell cycle regulation in Caulobacter - Wu, Jianguo (The National Academy of Sciences, 1998)
Cell differentiation and division in Caulobacter crescentus are regulated by a signal transduction pathway mediated by the histidine kinase DivJ and the essential response regulator DivK. Here we report genetic and biochemical evidence that the DivJ and DivK proteins function to control the activity of CtrA, a response regulator required for multiple cell cycle events, including flagellum biosynthesis, DNA replication, and cell division. Temperature-sensitive sokA (suppressor of divK) alleles were isolated as extragenic suppressors of a cold-sensitive divK mutation and mapped to the C terminus of the CtrA protein. The sokA alleles also suppress the lethal phenotype of a divK gene disruption and the cold-sensitive cell division phenotype of divJ mutants. The relationship between these signal transduction components and their target was further defined by demonstrating that the purified DivJ kinase phosphorylates CtrA, as well as DivK. Our studies also showed that phospho-CtrA activates transcription in vitro from the class II flagellar genes and that their promoters are recognized by the principal C. crescentus sigma factor σ(73). We propose that an essential signal transduction pathway mediated by DivJ, DivK, and CtrA coordinates cell cycle and developmental events in C. crescentus by regulating the level of CtrA phosphorylation and transcription from σ(73)-dependent class II gene promoters. Our results suggest that an unidentified phosphotransfer protein or kinase (X) is responsible for phosphoryl group transfer to CtrA in the proposed DivJ ⇒ DivK ⇒ X ⇒ CtrA phosphorelay pathway.